SUPER STOLARSKY 3 MEAN LABELING OF LINE GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
Let ???? be a graph with ???? vertices and ???? edges. Let ????: ????(????) → {1,2, … , ???? + ????} be an injective function. Fora vertex labeling f, the induced edge labeling ????(???? = ????????) is defined by ????(????) =⌈√????(????)2+????(????)????(????)+????(????)23⌉ ???????? ⌊√????(????)2+????(????)????(????)+????(????)23⌋,then the resulting edge labels are distinct. In this case ????is called Super Stolarsky-3 Mean labeling of ????. In this paper we investigate Super Stolarsky-3 Mean labelingof line graph.